Photo-thermal driving ion separation device and preparation method and application thereof
Through the optical driving ion separation device, the combination of the light thermal layer and the ion separation membrane is used to solve the problem of resource loss and impurities ion separation difficulty when extracting lithium from high magnesium/lithium salt lake brine. Environmental protection high -purity lithium extraction.
Patent Information
- Application Number
- CN202411498684.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The prior art faces problems such as lithium resource loss, waste liquid treatment and environmental impact when extracting lithium from salt lake brine with high magnesium/lithium ratio. In addition, traditional membrane separation technology cannot effectively separate sodium ions and potassium with similar hydration radius and charge properties. ion.
The light thermal -driven ion separation device is used. This device includes porous substrates, light thermal layers, and ion separation membranes. It absorbs light energy through the light and thermal layer to generate heat energy, drives water evaporation and achieves ionic separation. The ion separation membrane realizes the high purity extraction of lithium ions and the synchronization of impurities ions.
Achieve high -purity lithium from salt lake brine, and environmental protection, reducing energy consumption and operating costs, and solving the problem of lithium resource loss and impurities ion separation difficulties in traditional technologies.
Smart Images

Figure CN119368012A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a membrane technology, and in particular to a photothermal driven ion separation device and a preparation method and application thereof. Background Art
[0002] Lithium (Li) is an important non-renewable resource, and its supply shortage problem is becoming increasingly serious. According to statistics, about 70% of the world's extractable lithium is found in salt lake brines. However, this type of brine usually contains a large amount of magnesium ions, making the extraction of lithium difficult. Although China's salt lake reserves account for 80% of the world's available lithium reserves, due to the high magnesium / lithium ratio, traditional lithium extraction methods are not effective in actual operations. Currently, only a few salt lake resources with low magnesium / lithium ratios have been developed and utilized.
[0003] In order to solve the problem of lithium resource shortage, researchers have paid more and more attention to the technology of extracting lithium from brine with high magnesium / lithium ratio. At present, a variety of methods have been developed for lithium extraction, including tributyl phosphate / FeCl3 extraction, sodium metasilicate precipitation and lithium ion screening. Although these methods can effectively reduce the magnesium / lithium ratio in brine, they still face problems such as lithium resource loss, waste liquid treatment and environmental impact in practical applications. In addition, electrochemical recovery technology shows good selectivity and recovery rate in magnesium / lithium mixtures with high concentrations, but its large-scale application is limited due to the high cost of equipment, complex operation and relatively low recovery stability. Membrane separation technology is considered to be an effective solution for extracting lithium from brine with high magnesium / lithium ratio. Nanofiltration membrane combines size screening and charge repulsion principles and is expected to replace traditional methods. However, although the existing nanofiltration technology can well separate magnesium ions and lithium ions, it cannot effectively separate sodium ions and potassium ions with similar hydration radius and charge properties, which requires additional post-processing steps to purify the collected lithium products. In addition, high-concentration brine poses a challenge to the application of membrane separation technology because its high osmotic pressure difference requires the application of pressure that exceeds the membrane's tolerance. Therefore, traditional treatment processes often require dilution of high-concentration brine, and this pretreatment increases the complexity of the operation. At the same time, the lithium-rich solution obtained after nanofiltration membrane separation still needs to be further concentrated through energy-intensive processes to achieve effective lithium resource utilization. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a photothermal driven ion separation device that uses only sustainable energy to obtain high-purity lithium from salt lake brine, separates all interfering impurity ions in one step, is environmentally friendly, and reduces energy consumption and operating costs; another purpose of the present invention is to provide a preparation method and application of the photothermal driven ion separation device.
[0005] Technical solution: The photothermal driven ion separation device of the present invention comprises a porous matrix, a photothermal layer and an ion separation membrane; the photothermal layer is arranged on the first surface of the porous matrix; the ion separation membrane is arranged on the second surface of the porous matrix; the internal pore structure of the porous matrix connects the first surface and the second surface. The photothermal layer can absorb light energy and generate heat energy; the ion separation membrane has the function of selectively permeating different ions in the solution.
[0006] The relative positions of the first surface and the second surface are not limited. Preferably, the first surface is located at the upper side and the second surface is located at the lower side.
[0007] When the inner wall of the pore structure is made of hydrophilic material, the pore structure is a water channel; when the inner wall of the pore structure is not hydrophilic enough, a hydrophilic material is filled inside the pore structure, and the pore structure filled with hydrophilic material is used as a water channel. The water channel drives the water and permeable ions in the solution through the ion separation membrane and enters the pore structure of the porous matrix through capillary force; when in use, the water evaporates under the heating effect of the photothermal layer, and the remaining ions are deposited in the pore structure of the porous matrix.
[0008] The hole structure can be designed in the following two ways:
[0009] Method 1: The porous matrix itself is a water-absorbing material, or the inner wall of the pore structure is composed of a hydrophilic material. The size of the pore structure is micropores or nanopores. Through capillary force, water can be transported within the pore structure to the lower surface;
[0010] Method 2: Hydrophilic material is filled in the pore structure of the porous matrix. The material is provided with micropores or nanoscale water transport channels. Capillary force is the main power for water transmission. Under this action, water passes through the ion separation membrane to reach the photothermal layer, and evaporates in the photothermal layer. The ions that pass through the membrane are deposited in the water transport channels.
[0011] Preferably, the photothermal layer is a high molecular polymer light absorbing material.
[0012] Preferably, the photothermal layer is polypyrrole, light-absorbing gel or a blended polymer containing a black material, which is formed into a porous film by phase inversion or electrospinning process, or is directly formed in situ on the first surface of the porous matrix. The black material can be an organic polymer (such as polyaniline, PANI) or an inorganic material such as carbon nanotubes (CNTs), carbon black, carbon powder, graphene or MXene. The photothermal layer can also be a gel dispersed with photothermal nanomaterials, such as a hydrogel or an aerogel.
[0013] Preferably, the high molecular polymer light absorbing material is polypyrrole or polyaniline.
[0014] Preferably, when the inner wall of the pore structure itself is a hydrophilic material, the hydrophilic material is a sand core, and the pore size of the sand core is G1 to G6, preferably G6 specification; when the inner wall of the pore structure is not hydrophilic enough, the hydrophilic material is filled inside the pore structure, and the hydrophilic material is at least one of polyethersulfone (PES), polyvinylidene fluoride (PVDF), polyimide (PI), polyester (PP), polytetrafluoroethylene (PTFE), cellulose acetate (CA), polysulfone (PSF or PSU), polyacrylonitrile (PAN) and hydrogel. The nanoscale water transfer channel of the hydrophilic material can generate a pressure of hundreds of MPa to ensure the effective transmission of water.
[0015] Preferably, the ion separation membrane is a crown ether / graphene oxide inorganic nanofiltration membrane, which is in close contact with the second surface of the porous matrix; the crown ether / graphene oxide inorganic nanofiltration membrane comprises graphene oxide nanosheets and crown ethers; the crown ether is at least one of benzo-9-crown ether-3, benzo-12-crown ether-4, and dibenzo-14-crown ether-4.
[0016] The preparation method of the photothermal driven ion separation device described in the present invention comprises the following steps: a photothermal layer is formed on the first surface of a porous substrate by in-situ polymerization, and an ion separation membrane is in close contact with the second surface of the porous substrate; when the inner wall of the pore structure is not hydrophilic enough, a hydrophilic material is filled in the pore structure of the porous substrate, and the hydrophilic material is formed in the pore structure of the porous substrate by in-situ polymerization.
[0017] As a preferred method, in order to improve the performance stability of the device, at least one of the photothermal layer and the hydrophilic material is synthesized in situ to form an integrated structure, further improving the interlayer adhesion and overall stability. It is further preferred that both the photothermal layer and the hydrophilic material are synthesized in situ on the sand core to improve the layer adhesion and device stability.
[0018] Preferably, the specific preparation method of the photothermal layer is:
[0019] S01: preparing a light absorbing material monomer into an aqueous solution; the light absorbing material monomer is at least one of pyrrole and aniline;
[0020] S02 is provided with an oxidant aqueous solution;
[0021] S03 coating a light absorbing material monomer aqueous solution on a first surface of the porous substrate;
[0022] S04 coating an oxidant aqueous solution on the first surface of the porous substrate obtained in S03 and allowing to react;
[0023] S05 repeats step S02 and step S03 until a photothermal layer (2) having a required solar spectrum light absorption rate greater than 95% is formed.
[0024] Preferably, the oxidant is one of benzoyl peroxide, ammonium dichromate, hydrogen peroxide, ferric chloride, and ammonium persulfate.
[0025] Preferably, the mass fraction of the light absorbing material monomer in the aqueous solution is 0.5-2wt%; the mass fraction of the oxidant in the aqueous oxidant solution is 3.5-10wt%.
[0026] Further preferably, the photothermal layer forms polypyrrole (PPy) by alternately in-situ polymerization on the first surface of the sand core. Polypyrrole has excellent light absorption properties, can effectively improve the photothermal conversion efficiency of the device, and promote the evaporation of water. At the same time, polypyrrole has good compatibility with the sand core, can form a stable bonding strength, and ensure the structural firmness and long-term stability of the device. The specific preparation method is as follows: S01 configures an aqueous solution of pyrrole and an aqueous solution of ammonium persulfate, preferably the mass ratio of pyrrole to ammonium persulfate is (1-2): (2-5); S02 uniformly coats the pyrrole aqueous solution on the first surface of the porous substrate (sand core) to ensure that the liquid uniformly covers and penetrates the surface of the pore structure; S03 coats the ammonium persulfate aqueous solution on the first surface of the porous substrate that has been coated with the pyrrole solution, and stands for a sufficient time to allow the pyrrole monomer to undergo polymerization reaction under the action of the oxidant; S04 repeats the process of steps S02 and S03, alternately coating pyrrole and ammonium persulfate solutions until a photothermal layer of the desired thickness is formed. By repeated coating and in-situ polymerization, it is possible to ensure that the photothermal layer is evenly and densely covered on the surface of the substrate. In the present invention, pyrrole undergoes an oxidative polymerization reaction under the action of the oxidant ammonium persulfate: an electrically neutral pyrrole molecule is oxidized to a cationic radical after losing an electron. Subsequently, two molecules of cationic radicals combine to form a dication of dipolypyrrole. The dication generates electrically neutral dipolypyrrole through disproportionation. Dipolypyrrole continues to be oxidized to form longer polymer chains, gradually developing into chain PPy molecules with a degree of polymerization of n, and finally forming a stable photothermal layer. The reaction formula is:
[0027]
[0028] This reaction process continuously enhances the thickness and performance of the photothermal layer through alternating polymerization.
[0029] As a more specific embodiment, the preparation method of the photothermal layer is as follows: (1) preparing a pyrrole aqueous solution: the preferred content range of pyrrole in the pyrrole aqueous solution is 0.5-2wt%, and more preferably 1wt%. After adding pyrrole monomer to the aqueous solution, the solution is obtained by magnetic stirring for 10 minutes; (2) preparing an ammonium persulfate aqueous solution: the preferred content range of ammonium persulfate in the ammonium persulfate aqueous solution is 3.5-10wt%. When the content of pyrrole monomer is lower than this range, the self-polymerization reaction time of pyrrole will be significantly prolonged, resulting in a decrease in polymerization efficiency, and the polypyrrole layer formed on the surface of the sand core is not uniform and complete, affecting the performance of the photothermal layer. On the contrary, if the content of pyrrole monomer is too high, the polypyrrole generated during the polymerization process will fill the pores of the sand core, resulting in a significant decrease in the porosity of the sand core, a decrease in the pore size, and ultimately weakening the hydrophilicity of the sand core, thereby affecting the overall water transmission efficiency of the device. The preferred solution is prepared as follows: add 7g of ammonium persulfate white powder to 100mL of aqueous solution, stir magnetically for 10min and set aside; (3) Apply pyrrole solution: use a dropper to absorb an appropriate amount of pyrrole aqueous solution according to the surface area of the sand core, and evenly drip it onto the surface of the sand core. Subsequently, use a brush or other suitable tool to evenly apply the pyrrole solution to the surface of the sand core to ensure that the entire surface is completely wetted; (4) Use a dropper to absorb an appropriate amount of ammonium persulfate aqueous solution according to the area of the sand core, and evenly drip it onto the surface of the sand core. Use a brush to evenly apply the solution to ensure that the solution is in full contact with the pyrrole solution, and let it stand for 5-20min to allow the polypyrrole to polymerize in situ; (5) After gently wiping the residual solution on the surface of the sand core with dust-free paper, use a dropper again to absorb an appropriate amount of pyrrole solution, evenly drip it onto the surface of the sand core, and ensure that the film layer is completely wetted again. The reaction mixture was allowed to stand for 5-20 minutes, and the specific time can be flexibly adjusted according to the progress of the reaction; (6) the above steps (4) and (5) were repeated for a total of three cycles, and the last cycle ended with the addition of ammonium persulfate solution. Through this method, after alternately coating the pyrrole solution and the ammonium persulfate solution, three cycles were completed, and a photothermal layer for solar thermal conversion was formed by in-situ polymerization on the surface of the sand core.
[0030] As a preferred method, when the inner wall of the pore structure is not hydrophilic enough, the pore structure of the porous matrix (1) is filled with a hydrophilic material, and the hydrophilic material is prepared by in-situ synthesis in the pore structure. This setting can effectively adjust the pore size and wettability of the water transmission channel by regulating the polymer components, content or synthesis conditions. The hydrophilic material can be polymerized from two or more monomers, and the materials suitable for the present invention include but are not limited to polyethersulfone (PES), polyvinylidene fluoride (PVDF), polyimide (PI), polyester (PP), polytetrafluoroethylene (PTFE), cellulose acetate (CA), polysulfone (PSF or PSU), polyacrylonitrile (PAN) and hydrogel, etc. Polyethersulfone is preferably used as the main hydrophilic material, and the preparation method is as follows: S01 dissolves polyethersulfone particles, polyethyleneimine and polyethylene glycol in N, N-dimethylformamide (DMF) to form a uniform polymer solution; S02 injects the prepared polymer solution into the pore structure of the porous matrix to ensure that the pore structure is completely infiltrated by the solution. Subsequently, the matrix is sealed and maintained for a set time to allow the polymer to fully penetrate and stabilize; S03 takes out the treated porous matrix and places it in deionized water for a non-solvent induced phase inversion process. This step will form a uniformly distributed hydrophilic polymer inside the pore structure, ensuring that the water transmission channel has good hydrophilicity and adjustable pore size.
[0031] Preferably, the preparation method of the hydrophilic material is:
[0032] S01 dissolving polyethersulfone particles, polyethyleneimine and polyethylene glycol in N,N-dimethylformamide to prepare a uniform polymer solution;
[0033] S02 injecting the prepared polymer solution into the pore structure of the porous matrix, so that the polymer solution fully infiltrates the pore structure, ensuring that the inner wall of the pore is completely covered and maintains the infiltration state within a set time;
[0034] S03: taking the porous matrix out of the polymer solution and placing it in deionized water for non-solvent induced phase inversion, thereby forming a hydrophilic polymer in the pore structure of the porous matrix.
[0035] Further preferably, the preparation method of the hydrophilic material is: (1) adding polyethersulfone (PES) particles, polyethyleneimine (PEI) and polyethylene glycol (PEG) in N,N-dimethylformamide (DMF) solvent in sequence to prepare a uniform polymer solution with a certain viscosity. The polymer solution comprises 1-10 wt % polyethersulfone particles, 0.5-8 wt % polyethyleneimine and 1-5 wt % polyethylene glycol. The polymer solution is magnetically stirred at 25-55° C. for 8-16 h to ensure that all components are fully dissolved and form a uniform solution, and then allowed to stand at room temperature for degassing for 8-16 h for standby use; (2) slowly dripping the prepared polymer solution onto the microporous sand core to ensure that the solution completely infiltrates the pore structure of the sand core. In order to ensure that the solution fully diffuses and penetrates in the pores, the sand core is sealed for 24 h; (3) taking out the microporous sand core that is completely infiltrated with the polymer solution, quickly placing it in deionized water for water bath non-solvent induced phase inversion, and standing for 24 h to complete the phase inversion of the polymer. After the phase inversion is completed, the pore structure of the sand core is filled with the polymer; (4) taking out the sand core that is completely infiltrated with the polymer solution from the sealing container, and quickly transferring it to deionized water for water bath non-solvent induced phase inversion. During the phase inversion process, DMF and PEG are dissolved in water, so that polyethersulfone forms a three-dimensional macromolecular network gel in the pore structure. The phase inversion is completed by standing for 24 hours. At this time, the pores of the sand core are filled with hydrophilic polymers, forming water channels with good transmission performance.
[0036] Further preferably, the polymer solution in step (1) is obtained by dissolving 7wt% of polyethersulfone (PES) particles, 2.5wt% of polyethyleneimine (PEI) and 1.5wt% of polyethylene glycol (PEG) in DMF solvent, and the polymer solution is magnetically stirred at 45°C for 12h and allowed to stand for degassing for 12h. The type (single chain or branched) and molecular weight of polyethyleneimine are not limited, preferably the molecular weight of polyethyleneimine is 80000 and the molecular weight of polyethylene glycol is 1000, which can provide more positively charged amino groups in the polymer film formed subsequently, improve the adhesion of the in-situ polymerized nanofiltration layer, and also improve the hydrophilicity of the polymer film and the water flux of the polymer film. The type and molecular weight of the non-solvent additive are not limited, and the type of solvent used is not limited.
[0037] Preferably, the specific preparation method of the ion separation membrane is:
[0038] S01: preparing an aqueous solution of graphene oxide as a first solution; preparing a dimethylformamide solution of crown ether as a second solution;
[0039] S02: the first solution and the second solution are mixed and ultrasonically dispersed to obtain a mixed solution, and the mixed solution is filtered on a filter membrane to obtain an ion separation membrane.
[0040] Preferably, the filter membrane is one of a polyethersulfone membrane, a cellulose acetate membrane, a nitrocellulose membrane, a polycarbonate membrane, a polytetrafluoroethylene membrane, and a polyvinylidene fluoride membrane.
[0041] Further preferably, the filter membrane is a polyethersulfone membrane.
[0042] Preferably, the pore size of the polyethersulfone membrane is 220-450 nm.
[0043] Preferably, the mass fraction of the aqueous solution of graphene oxide in the first solution is 1-2 mg / ml, and the mass fraction of the crown ether in the second solution is 10-200 mg / ml, preferably 50 mg / ml.
[0044] Further preferably, the specific preparation method of the ion separation membrane is as follows: (1) preparing a graphene oxide aqueous solution containing 1-2 mg / ml and a dimethylformamide solution containing 10-200 mg / ml of benzo-12-crown ether-4; (2) mixing the two in a ratio of (10-20):(1-5) at 20-40°C for 1-5 hours to obtain a completely dispersed mixed solution; (3) using a polyethersulfone membrane as a filter membrane, filtering 5-20 ml of the mixed solution through a solvent filter, and filtering until the surface is completely dried; (4) removing the filtered filter membrane from the solvent filter, and vacuum drying it at 50-60°C for 4-12 hours to obtain an ion separation membrane.
[0045] The photothermal driven ion separation device of the present invention is used in ion extraction. The photothermal driven ion separation device floats on the surface of a solution and directly contacts the solution through its ion separation membrane to achieve selective permeation and separation of ions.
[0046] Preferably, the specific application method is as follows: during use, the device floats on the surface of the solution to be extracted, with the first surface facing upward to fully absorb sunlight and generate heat, and the second surface in contact with the solution to be extracted to promote the separation and extraction of ions. Water molecules enter the pore structure of the porous matrix from the solution to be extracted through the ion separation membrane, and are converted into water vapor after being heated and escape from above the photothermal layer. At this time, the ions are deposited in the pores of the porous matrix. After the device is finished working, the ions deposited in the pores are dissolved in water by immersing the device in deionized water or rinsing the pore structure with deionized water, thereby completing the ion extraction process.
[0047] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0048] 1. No external energy is required: The photothermal driven ion separation device of the present invention relies on sunlight and capillary forces within the porous structure as the transmission power of water and ions, achieving the advantages of energy saving and environmental protection and reducing dependence on external energy.
[0049] 2. Strong controllability: By independently synthesizing hydrophilic materials in the device, the hydrophilicity and pore size of the material can be flexibly controlled, thereby adjusting the capillary force to adapt to different application scenarios and needs.
[0050] 3. Improve evaporation efficiency: The photothermal layer formed in situ on the porous substrate ensures efficient heat transfer on the device, further improves the evaporation efficiency of water vapor, and enhances the overall performance of the device.
[0051] 4. High-efficiency filtration: Compared with traditional nanofiltration membranes, the pore size screening effect of crown ethers can specifically identify ions, adapt to the separation needs of different ions, and improve the overall separation efficiency.
[0052] 5. Sustainable and cost-effective: The present invention directly extracts high-purity lithium from salt lake brine through interfacial solar evaporation technology, which is an environmentally friendly solution that reduces dependence on traditional energy-intensive processes, reduces energy consumption and operating costs.
[0053] 6. Efficient treatment of salt lake brine: The device can directly recover lithium resources from salt lake brine with a high magnesium-lithium ratio and multiple interfering impurity ions. Compared with the existing salt lake ion extraction technology, the device of the present invention can not only realize the cyclic crystallization collection of lithium salts, but also achieve a one-step synchronous separation of lithium ions and all other interfering ions, solving the problem that traditional technology cannot separate sodium ions and potassium ions with similar radius and charge. In addition, the device also ensures the environmental protection and economic benefits of the extraction process. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is a structural diagram of the photothermal driven ion separation device of the present invention;
[0055] Figure 2 This is a structural diagram of the present invention after the hollow splint encapsulates the photothermal driven ion separation device;
[0056] Figure 3 The evaporation rate of pure water in different salt solutions of the photothermal driven ion separation device in Example 1 of the present invention under the illumination of one sun (1 sun);
[0057] Figure 4 The separation factors of lithium-magnesium, lithium-potassium and lithium-sodium of the photothermal driven ion separation device in Example 1 of the present invention in salt solutions of different concentrations;
[0058] Figure 5 is the crystallization rate of lithium chloride in salt solutions of different concentrations of the photothermal driven ion separation device in Example 1 of the present invention;
[0059] Figure 6The separation factors of lithium magnesium, lithium potassium and lithium sodium in 1 g / L salt solution of the photothermal driven ion separation device in Example 1 of the present invention and the photothermal driven ion separation device in Comparative Example 1 of the present invention;
[0060] Figure 7 The crystallization rates of lithium chloride in 1 g / L salt solution of the photothermal driven ion separation device in Example 1 of the present invention and the photothermal driven ion separation device in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0062] The photothermal driven ion separation device of the present invention is as follows Figure 1 As shown, it includes a porous matrix 1. The porous matrix 1 has a first surface and a second surface that are arranged oppositely, and a pore structure is evenly distributed thereon, which penetrates the first surface and the second surface as a channel. A photothermal layer 2 is arranged on the first surface, and the photothermal layer 2 is a porous membrane layer; an ion separation membrane 3 is arranged in close contact on the second surface, and the nanofiltration membrane layer can selectively pass specific ions, thereby realizing the effective separation of target ions and other ions. The inside of the pore structure is filled with a hydrophilic material, and a water transport channel is arranged on the hydrophilic material. The water transport channel is a nanoscale channel, preferably with a size range of 10-220nm, which can generate a megapascal pressure of more than 18MPa. During use, the first surface faces upward as the upper surface, and the second surface faces downward as the lower surface. The device is suspended in the solution to be extracted, the lower surface is in contact with the solution, and the upper surface is not in contact with the solution. The water and target ions in the solution to be extracted pass through the nanofiltration membrane to the hydrophilic material and are transmitted inside the hydrophilic material. Under the action of the photothermal layer 2, the water absorbs heat and is converted into water vapor, and escapes through the photothermal layer 2. At the same time, the ions to be extracted are deposited in the hydrophilic material and eventually form solid crystals. There is no restriction on the extraction method of the solid crystals. The solid crystals can be dissolved by soaking the device or separated by washing the device with deionized water. In addition, the solid crystals can be directly separated from the device by other methods.
[0063] In order to achieve stable floating of the device in the solution, the porous matrix 1 in the present invention can be made of a material with buoyancy properties. The device can float on the surface of the solution through its own buoyancy; in addition, a buoyancy member can be provided on the device to enhance its floating ability. As shown in Example 2, the embodiment uses a hollow splint 4 with buoyancy, which is provided on both sides of the device, and a gasket is provided between the hollow splint 4 and the device to clamp the device. The hollow splint 4 is an annular structure, which can form an effective support around the device.
[0064] In the embodiment, the porous substrate 1 is a sand core containing micropores, the thickness of the sand core is 3 mm, the pore diameter of the sand core is G6, and the pore diameter range is 1.2 to 10 μm.
[0065] The above devices can be used to separate ions with different charges or pore sizes, such as allowing Li + Monovalent ions pass through and block other interfering impurity ions, such as SO4 2- , Ca 2+ and Mg 2+ Divalent ions such as Na + , K + As an application, the device can effectively separate lithium ions from a mixed solution of lithium ions, magnesium ions, sodium ions, and potassium ions, so that lithium ions and lithium salts are finally crystallized and precipitated on the top of the photothermal layer 2, thereby realizing the extraction of lithium ions.
[0066] Example 1
[0067] The method for preparing the device comprises the following steps:
[0068] Step 1: In-situ synthesis of the photothermal layer 2 on the first surface of the sand core, the synthesis method is:
[0069] (1) Add 0.5 g of pyrrole (analytical grade) to 99.5 mL of aqueous solution and stir magnetically for 10 min to obtain a 0.5 wt% pyrrole aqueous solution;
[0070] (2) adding 7 g of ammonium persulfate powder to 92 mL of aqueous solution and magnetically stirring for 10 min to obtain a 7 wt % ammonium persulfate aqueous solution;
[0071] (3) Use a dropper to absorb a certain amount (determined according to the area of the selected sand core) of pyrrole aqueous solution and drop it onto the surface of the sand core. The amount of pyrrole aqueous solution per unit area of the sand core is 0.5 mL / m 2 , and then use a brush to apply it evenly to ensure that the entire sand core surface is wet;
[0072] (4) Use a dropper to absorb a certain amount (determined according to the area of the selected sand core) of ammonium persulfate aqueous solution and drop it onto the surface of the sand core. The amount of ammonium persulfate aqueous solution added per unit area of the sand core is 0.5 mL / m 2 , and apply it evenly with a brush, and let it stand for 2 minutes. During this process, pyrrole undergoes polymerization to form polypyrrole;
[0073] (5) After wiping the residual aqueous solution on the surface of the sand core with dust-free paper, 2 Add the pyrrole aqueous solution to the sand core to completely wet the membrane surface, and let it react for 2 minutes;
[0074] (6) Continue to repeat the above steps (4) and (5) for a total of three cycles, and terminate the reaction by adding the ammonium persulfate solution. At this point, the photothermal layer 2 for solar thermal conversion is prepared by the in-situ polymerization reaction on the surface of the sand core.
[0075] Step 2: Fill the pore structure of the sand core with hydrophilic material, the preparation method is:
[0076] (1) Adding polyethersulfone particles, polyethyleneimine and polyethylene glycol to N,N-dimethylformamide (DMF) solvent to prepare a polymer solution of a certain viscosity, wherein the concentration of polyethersulfone particles in the polymer solution is 7 wt %, the molecular weight of polyethyleneimine is 80,000 and the concentration is 2.5 wt %, and the molecular weight of polyethylene glycol is 1,000 and the concentration is 1.5 wt %. The polymer solution is magnetically stirred at 40° C. for 12 h, and then allowed to stand at room temperature for 12 h for degassing, and then used;
[0077] (2) slowly dripping the prepared polymer solution from the second surface into the microporous sand core pore structure to completely infiltrate it, and sealing it for 24 hours;
[0078] (3) taking out the completely soaked microporous sand core containing the polymer solution, quickly placing it in deionized water for water bath non-solvent induced phase transformation, and letting it stand for 24 hours to complete the phase transformation of the polymer;
[0079] (4) Take out the polymer-filled microporous sand core, transfer it to new deionized water and store it for later use.
[0080] Step 3: preparing crown ether / graphene oxide inorganic nanofiltration membrane, the preparation method is:
[0081] (1) preparing an aqueous solution containing 1 mg / ml graphene oxide, and magnetically stirring at 25° C. for 4 h to obtain a completely dispersed and uniform graphene oxide aqueous solution;
[0082] (2) preparing a dimethylformamide solution containing 50 mg of benzo-12-crown-4, and magnetically stirring at 25° C. for 4 h to obtain a dimethylformamide solution in which benzo-12-crown-4 was completely dissolved;
[0083] (3) mixing the graphene oxide aqueous solution and the benzo-12-crown-4-dimethylformamide solution in a mass ratio of 10:1, and magnetically stirring at 25° C. for 4 h to obtain a uniformly mixed solution;
[0084] (4) Take 10 ml of the mixed solution and perform vacuum filtration in a solvent filter using a polyethersulfone membrane with a pore size of 220 nm as the substrate until the surface water is completely drained;
[0085] (5) The filtered membrane was peeled off from the solvent filter and vacuum dried at 60° C. for 12 h to obtain the crown ether / graphene oxide photothermal ion separation membrane 3.
[0086] Example 2
[0087] The method for preparing the device comprises the following steps:
[0088] Step 1: In-situ synthesis of the photothermal layer 2 on the first surface of the sand core, the synthesis method is:
[0089] (1) Add 2 g of aniline (analytical grade) to 98 mL of aqueous solution and stir magnetically for 10 min to obtain an aniline aqueous solution with a mass fraction of 2 wt %;
[0090] (2) adding 3.5 g of ferric chloride powder to 96.5 mL of the aqueous solution and stirring magnetically for 10 min to obtain a 3.5 wt % ferric chloride aqueous solution;
[0091] (3) Use a dropper to absorb a certain amount (determined according to the area of the selected sand core) of aniline aqueous solution and drop it onto the surface of the sand core. The amount of aniline aqueous solution per unit area of the sand core is 0.5 mL / m 2 , and then use a brush to apply it evenly to ensure that the entire sand core surface is wet;
[0092] (4) Use a dropper to draw a certain amount (determined according to the area of the selected sand core) of ferric chloride aqueous solution and drop it onto the surface of the sand core. The amount of ammonium persulfate aqueous solution added per unit area of the sand core is 0.5 mL / m 2 , and apply it evenly with a brush, and let it stand for 2 minutes. During this process, aniline undergoes polymerization to form polyaniline;
[0093] (5) After wiping the residual aqueous solution on the surface of the sand core with dust-free paper, 2 Add aniline aqueous solution to the sand core to completely wet the membrane surface, and let it react for 2 minutes;
[0094] (6) Continue to repeat the above steps (4) and (5) for a total of three cycles, and terminate the reaction by adding the ferric chloride solution. At this point, the photothermal layer 2 for solar thermal conversion is prepared by the in-situ polymerization reaction on the surface of the sand core.
[0095] Step 2: Fill the pore structure of the sand core with hydrophilic material, the preparation method is:
[0096] (1) Adding polyethersulfone particles, polyethyleneimine and polyethylene glycol to N,N-dimethylformamide (DMF) solvent to prepare a polymer solution of a certain viscosity, wherein the concentration of polyethersulfone particles in the polymer solution is 10 wt %, the molecular weight of polyethyleneimine is 100000, and the concentration is 8 wt %, and the molecular weight of polyethylene glycol is 2000, and the concentration is 5 wt %. The polymer solution is magnetically stirred at 40° C. for 12 h, and then allowed to stand at room temperature for degassing for 12 h for standby use;
[0097] (2) slowly dripping the prepared polymer solution from the second surface into the microporous sand core pore structure to completely infiltrate it, and sealing it for 24 hours;
[0098] (3) taking out the completely soaked microporous sand core containing the polymer solution, quickly placing it in deionized water for water bath non-solvent induced phase transformation, and letting it stand for 24 hours to complete the phase transformation of the polymer;
[0099] (4) Take out the polymer-filled microporous sand core, transfer it to new deionized water and store it for later use.
[0100] Step 3: preparing crown ether / graphene oxide inorganic nanofiltration membrane, the preparation method is:
[0101] (1) preparing an aqueous solution containing 1.5 mg / ml graphene oxide, and magnetically stirring at 25° C. for 4 h to obtain a completely dispersed and uniform graphene oxide aqueous solution;
[0102] (2) preparing a dimethylformamide solution containing 10 mg of dibenzo-14-crown-4, and magnetically stirring at 25° C. for 4 h to obtain a dimethylformamide solution in which dibenzo-14-crown-4 was completely dissolved;
[0103] (3) mixing the graphene oxide aqueous solution and the dibenzo-14-crown-4-dimethylformamide solution in a mass ratio of 10:5, and magnetically stirring at 25° C. for 4 h to obtain a uniformly mixed solution;
[0104] (4) Take 10 ml of the mixed solution and perform vacuum filtration in a solvent filter using a polyethersulfone membrane substrate with a pore size of 220 nm until the surface water is completely drained;
[0105] (5) The filtered membrane was peeled off from the solvent filter and vacuum dried at 60° C. for 12 h to obtain the crown ether / graphene oxide photothermal ion separation membrane 3.
[0106] Example 3
[0107] The method for preparing the device comprises the following steps:
[0108] Step 1: In-situ synthesis of the photothermal layer 2 on the first surface of the sand core, the synthesis method is:
[0109] (1) Add 1 g of pyrrole and aniline (analytical grade, mass ratio of 1:1) to 99 mL of aqueous solution, and stir magnetically for 10 min to obtain a mixed aqueous solution of pyrrole and aniline with a mass fraction of 1 wt %;
[0110] (2) adding 5 g of ammonium dichromate powder to 95 mL of the aqueous solution and stirring magnetically for 10 min to obtain a 5 wt % ammonium dichromate aqueous solution;
[0111] (3) Use a dropper to absorb a certain amount (determined according to the area of the selected sand core) of the pyrrole and aniline mixed aqueous solution and drop it onto the surface of the sand core. The amount of the pyrrole and aniline mixed aqueous solution per unit area of the sand core is 0.5 mL / m 2 , and then use a brush to apply it evenly to ensure that the entire sand core surface is wet;
[0112] (4) Use a dropper to absorb a certain amount (determined according to the area of the selected sand core) of ammonium dichromate aqueous solution and drop it onto the surface of the sand core. The amount of ammonium dichromate aqueous solution added per unit area of the sand core is 0.5 mL / m 2 , and use a brush to apply it evenly, and let it stand for 2 minutes. During this process, pyrrole and aniline undergo polymerization to form a pyrrole-aniline copolymer. The reaction formula is as follows;
[0113] (5) After wiping the residual aqueous solution on the surface of the sand core with dust-free paper, 2 Add the mixed aqueous solution of pyrrole and aniline to the sand core to completely wet the membrane surface, and let it react for 2 minutes;
[0114] (6) Continue to repeat the above steps (4) and (5) for a total of three cycles, and terminate the reaction by adding the ammonium dichromate solution. At this point, the photothermal layer 2 for solar thermal conversion is prepared by the in-situ polymerization reaction on the surface of the sand core.
[0115] Step 2: Fill the pore structure of the sand core with hydrophilic material, the preparation method is:
[0116] (1) Adding polyethersulfone particles, polyethyleneimine and polyethylene glycol to N,N-dimethylformamide (DMF) solvent to prepare a polymer solution of a certain viscosity, wherein the concentration of polyethersulfone particles in the polymer solution is 1wt%, the molecular weight of polyethyleneimine is 120000, and the concentration is 1wt%, and the molecular weight of polyethylene glycol is 5000, and the concentration is 5wt%. The polymer solution is magnetically stirred at 40°C for 12h, and then allowed to stand at room temperature for degassing for 12h for standby use;
[0117] (2) slowly dripping the prepared polymer solution from the second surface into the microporous sand core pore structure to completely infiltrate it, and sealing it for 24 hours;
[0118] (3) taking out the completely soaked microporous sand core containing the polymer solution, quickly placing it in deionized water for water bath non-solvent induced phase transformation, and letting it stand for 24 hours to complete the phase transformation of the polymer;
[0119] (4) Take out the polymer-filled microporous sand core, transfer it to new deionized water and store it for later use.
[0120] Step 3: preparing crown ether / graphene oxide inorganic nanofiltration membrane, the preparation method is:
[0121] (1) preparing an aqueous solution containing 2 mg / ml graphene oxide, and magnetically stirring at 25° C. for 4 h to obtain a completely dispersed and uniform graphene oxide aqueous solution;
[0122] (2) preparing a dimethylformamide solution containing 200 mg of benzo-9-crown-3, stirring under magnetic stirring at 25° C. for 4 h, and obtaining a dimethylformamide solution of completely dissolved benzo-9-crown-3;
[0123] (3) mixing the graphene oxide aqueous solution and the benzo(9-crown-3-dimethylformamide) solution in a mass ratio of 20:5, and magnetically stirring at 25° C. for 4 h to obtain a uniformly mixed solution;
[0124] (4) Take 10 ml of the mixed solution and perform vacuum filtration in a solvent filter using a polyethersulfone membrane with a pore size of 220 nm as the substrate until the surface water is completely drained;
[0125] (5) The filtered membrane was peeled off from the solvent filter and vacuum dried at 60° C. for 12 h to obtain the crown ether / graphene oxide photothermal ion separation membrane 3.
[0126] Example 4
[0127] This embodiment uses a sand core with hydrophilic channels, and no further filling of hydrophilic polymer is required. The device preparation method includes the following steps:
[0128] Step 1: In-situ synthesis of the photothermal layer 2 on the first surface of the sand core, the synthesis method is:
[0129] (1) Add 1 g of aniline (analytical grade) to 98 mL of aqueous solution and stir magnetically for 10 min to obtain an aniline aqueous solution with a mass fraction of 1 wt%;
[0130] (2) adding 5 g of ferric chloride powder to 95 mL of the aqueous solution and stirring magnetically for 10 min to obtain a 5 wt% ferric chloride aqueous solution;
[0131] (3) Use a dropper to absorb a certain amount (determined according to the area of the selected sand core) of aniline aqueous solution and drop it onto the surface of the sand core. The amount of aniline aqueous solution per unit area of the sand core is 0.5 mL / m 2, and then use a brush to apply it evenly to ensure that the entire sand core surface is wet;
[0132] (4) Use a dropper to draw a certain amount (determined according to the area of the selected sand core) of ferric chloride aqueous solution and drop it onto the surface of the sand core. The amount of ammonium persulfate aqueous solution added per unit area of the sand core is 0.5 mL / m 2 , and apply it evenly with a brush, and let it stand for 2 minutes. During this process, pyrrole undergoes polymerization to form polyaniline;
[0133] (5) After wiping the residual aqueous solution on the surface of the sand core with dust-free paper, 2 Add aniline aqueous solution to the sand core to completely wet the membrane surface, and let it react for 2 minutes;
[0134] (6) Continue to repeat the above steps (4) and (5) for a total of three cycles, and terminate the reaction by adding the ferric chloride solution. At this point, the photothermal layer 2 for solar thermal conversion is prepared by the in-situ polymerization reaction on the surface of the sand core.
[0135] Step 2: preparing crown ether / graphene oxide inorganic nanofiltration membrane, the preparation method is:
[0136] (1) preparing an aqueous solution containing 1 mg / ml graphene oxide, and magnetically stirring at 25° C. for 4 h to obtain a completely dispersed and uniform graphene oxide aqueous solution;
[0137] (2) preparing a dimethylformamide solution containing 50 mg of dibenzo-14-crown-4, and stirring magnetically at 25° C. for 4 h to obtain a dimethylformamide solution in which dibenzo-14-crown-4 was completely dissolved;
[0138] (3) mixing the graphene oxide aqueous solution and the dibenzo-14-crown-4-dimethylformamide solution in a mass ratio of 10:1, and magnetically stirring at 25° C. for 4 h to obtain a uniformly mixed solution;
[0139] (4) Take 10 ml of the mixed solution and perform vacuum filtration in a solvent filter using a polyethersulfone membrane with a pore size of 220 nm as the substrate until the surface water is completely drained;
[0140] (5) The filtered membrane was peeled off from the solvent filter and vacuum dried at 60° C. for 12 h to obtain the crown ether / graphene oxide photothermal ion separation membrane 3.
[0141] Comparative Example 1
[0142] It only contains the ion separation membrane 3, does not contain the photothermal layer 2, and no crown ether molecules are introduced into the ion separation membrane 3. The preparation steps are as follows:
[0143] (1) preparing an aqueous solution containing 1 mg / ml graphene oxide, and magnetically stirring at 25° C. for 4 h to obtain a completely dispersed and uniform graphene oxide aqueous solution;
[0144] (2) taking 10 ml of graphene oxide aqueous solution, using an AAO membrane with a pore size of 100 nm as the substrate, and vacuum filtering in a solvent filter until the surface water is completely drained;
[0145] (3) The filtered membrane was peeled off from the solvent filter and vacuum dried at 60° C. for 12 h to obtain the ion separation membrane 3 of Comparative Example 1;
[0146] (4) The ion separation membrane 3 of Comparative Example 1 prepared is placed in close contact with any surface of the sand core for use.
[0147] test:
[0148] Prepare the following solution:
[0149] Solution 1: A mixed saline solution of magnesium chloride, sodium chloride, potassium chloride and lithium chloride with a total concentration of 1 g / L, wherein the mass ratio of each ion is 1:1:1:1.
[0150] Solution 2: A mixed saline solution of magnesium chloride, sodium chloride, potassium chloride and lithium chloride with a total concentration of 2 g / L, wherein the mass ratio of each ion is 1:1:1:1.
[0151] Solution 3: A mixed saline solution of magnesium chloride, sodium chloride, potassium chloride and lithium chloride with a total concentration of 3 g / L, wherein the mass ratio of each ion is 1:1:1:1.
[0152] Solution 4: A mixed saline solution of magnesium chloride, sodium chloride, potassium chloride and lithium chloride with a total concentration of 4 g / L, wherein the mass ratio of each ion is 1:1:1:1.
[0153] Solution 5: A mixed saline solution of magnesium chloride, sodium chloride, potassium chloride and lithium chloride with a total concentration of 5 g / L, wherein the mass ratio of each ion is 1:1:1:1.
[0154] The device described in Example 1 is packaged with a hollow splint 4 and a gasket, wherein the hollow splint 4 and the gasket are both annular structures fixed around the upper and lower surfaces of the device. The hollow splint 4 has buoyancy, so that the device can float on the water surface. The obtained device is placed in a mixed salt solution of solution 1 to 5 respectively, ensuring that the crown ether / graphene oxide inorganic ion separation membrane 3 is in contact with the solution. Subsequently, the lithium extraction efficiency of the device is tested under one sunlight intensity, and the experimental duration is 72 hours.
[0155] In the above test, the water evaporation rate, separation factor and lithium chloride crystallization rate of the device are evaluated. Taking lithium and magnesium ions as an example, the separation factor is calculated as follows: separation factor = ratio of the mass of lithium and magnesium ions after separation / ratio of the mass of lithium and magnesium ions before separation. If the mass ratio of lithium ions to magnesium ions in the salt solution to be extracted is 1:1, and it is assumed that the mass ratio of lithium ions to magnesium ions entering the sand core pore structure is 15:1, then the separation ratio is (15:1) / (1:1)=15.
[0156] The calculation method of lithium chloride crystallization rate is: the mass of lithium chloride powder collected by the device per unit area through solar energy drive in unit time. In the present invention, the lithium chloride powder collected by the device is dissolved in a certain volume of aqueous solution, and the mass concentration of lithium ions in the aqueous solution is tested by inductively coupled plasma spectrometer, and then the mass of lithium chloride powder is deduced. For example, if the lithium ion concentration in the aqueous solution is 5 mg / L and the volume of the aqueous solution is 0.1L, the mass of lithium is: mass of lithium = 5mg / L×0.1L = 0.5mg
[0157] Test results such as Figures 3 to 5 As shown. Figure 3-4 It can be seen that with the increase of the total concentration of the mixed brine solution, the water evaporation rate and the separation factor remain basically unchanged. Figure 5 It shows that as the concentration of the mixed salt solution increases, the crystallization rate of lithium chloride increases, indicating that the device can adapt to salt solutions of various concentrations. In high-concentration salt solutions, this feature is conducive to increasing the crystallization rate of salt.
[0158] The separation factor and lithium chloride crystallization rate of comparative example 1 were tested using solution 1. The results are as follows: Figure 6 and Figure 7 As shown. Figure 6 It can be seen that since comparative example 1 does not add a crown ether with a specific recognition function for lithium ions, it only has a limited separation effect on magnesium ions, and has no separation effect on sodium ions and potassium ions, and the separation factor is close to 1. Example 1 has a good separation effect on all ions. Figure 7 It can be seen that due to the absence of the photothermal layer 2, the crystallization rate of lithium chloride in Comparative Example 1 is much lower than that in Example 1.
Claims
1. A photothermal driven ion separation device, characterized in that: It comprises a porous substrate (1), a photothermal layer (2) and an ion separation membrane (3); the photothermal layer (2) is arranged on a first surface of the porous substrate (1); the ion separation membrane (3) is arranged on a second surface of the porous substrate (1); and the internal pore structure of the porous substrate (1) is connected to the first surface and the second surface; When the inner wall of the pore structure itself is a hydrophilic material, the pore structure is a water transport channel; When the inner wall of the pore structure is not hydrophilic enough, a hydrophilic material is filled inside the pore structure, and the pore structure filled with the hydrophilic material serves as a water transport channel.
2. The photothermal driven ion separation device according to claim 1, characterized in that: The photothermal layer (2) is a high molecular polymer light absorbing material.
3. The photothermal driven ion separation device according to claim 1, characterized in that: When the inner wall of the pore structure itself is a hydrophilic material, the hydrophilic material is a sand core; when the inner wall of the pore structure is not hydrophilic enough, a hydrophilic material is filled inside the pore structure, and the hydrophilic material is at least one of polyethersulfone (PES), polyvinylidene fluoride (PVDF), polyimide (PI), polyester (PP), polytetrafluoroethylene (PTFE), cellulose acetate (CA), polysulfone (PSF or PSU), polyacrylonitrile (PAN) and hydrogel.
4. The photothermal driven ion separation device according to claim 1, characterized in that: The ion separation membrane (3) is a crown ether / graphene oxide inorganic nanofiltration membrane, which is in close contact with the second surface of the porous substrate (1); the crown ether / graphene oxide inorganic nanofiltration membrane comprises graphene oxide nanosheets and crown ether; the crown ether is at least one of benzo 9-crown ether-3, benzo 12-crown ether-4, and dibenzo 14-crown ether-4.
5. A method for preparing a photothermal driven ion separation device, characterized in that: The following steps are involved: The photothermal layer (2) is formed on the first surface of the porous substrate (1) by in-situ polymerization, and the ion separation membrane (3) is in close contact with the second surface of the porous substrate (1); when the inner wall of the pore structure is not hydrophilic enough, the pore structure of the porous substrate (1) is filled with a hydrophilic material, and the hydrophilic material is formed in the pore structure of the porous substrate (1) by in-situ polymerization.
6. The method for preparing the photothermal driven ion separation device according to claim 5, characterized in that: The specific preparation method of the photothermal layer (2) is: S01: preparing a light absorbing material monomer into an aqueous solution, wherein the light absorbing material monomer is at least one of pyrrole and aniline; S02 is provided with an oxidant aqueous solution; S03 coating a light absorbing material monomer aqueous solution on a first surface of the porous substrate (1); S04 coating an aqueous oxidant solution on the first surface of the porous substrate (1) obtained in S03 and allowing to react; S05 repeats step S02 and step S03 until a photothermal layer (2) having a required solar spectrum light absorption rate greater than 95% is formed.
7. The method for preparing a photothermal driven ion separation device according to claim 6, characterized in that: The mass fraction of the light absorbing material monomer in the aqueous solution is 0.5-2wt%; the mass fraction of the oxidant in the aqueous oxidant solution is 3.5-10wt%.
8. The method for preparing a photothermal driven ion separation device according to claim 5, characterized in that: The specific preparation method of the ion separation membrane (3) is as follows: an aqueous solution of graphene oxide is prepared as the first solution; a dimethylformamide solution of crown ether is prepared as the second solution; the first solution and the second solution are mixed and ultrasonically dispersed to obtain a mixed solution, and the mixed solution is filtered on a filter membrane to obtain the ion separation membrane (3).
9. The method for preparing a photothermal driven ion separation device according to claim 8, characterized in that: The mass fraction of the aqueous solution of graphene oxide in the first solution is 1-2 mg / ml, and the mass fraction of the crown ether in the second solution is 10-200 mg / ml.
10. Use of the photothermally driven ion separation device according to any one of claims 1 to 4 or the photothermally driven ion separation device prepared by the preparation method according to any one of claims 5 to 9 in ion extraction.
Citation Information
Patent Citations
Ion separation device, method and application
CN115353247A
Super-hydrophilic 3D printing three-dimensional porous photothermal conversion component and preparation method and application thereof
CN116282280A
Composite membrane for selectively separating lithium ions as well as preparation method and application of composite membrane
CN118001952A
Preparation of hydrophilic polyvinylidene fluoride microporous membrane
CN1704152A